Special Issue “Risk, Ruin and Survival: Decision Making in Insurance and Finance” - Jiandong Ren; Kristina Sendova; Ričardas Zitikis (Risks, 2019)
It has been six years since Editor-in-Chief Steffensen (2013) wrote in his editorial that “to Risks inclusiveness, inter-disciplinarity, and open-mindedness is the very starting point [...]